Laju Dekomposisi Serasah Daun Rhizophora apiculata dan Analisis Unsur Hara C, N dan P di Pantai Serambi Deli Kecamatan Pantai Labu Kabupaten Deli Serdang - Fatimah Murni; Yunasfi Djayus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Mangrove ecosystems have ecological functions, one of them is the contributor organic matter in aquatic through the production litter that being decomposed. This study aims to measure the rate leaf litter decomposition and nutrient content C, N and P. The research was conducted from July - October 2014 at the Serambi Deli Beach Pantai Labu distric, Sumatera Utara. The rate of leaf litter decomposition were used 21 bags litter bag at each station. Methods for determining the elements C is a Walkley and Black method, element N is a Kjehdahl method and element P is dry ashing method with HCL 25% extracting. The results measurements of litter decomposition rate was highest on day 15 and 30 was 1.01 g/day and the lowest at day 105 was 0.41 g/day. The value of the decomposition rate constant (k) leaf litter on the station I, II and III respectively amounted to 0.023, 0.024 and 0.025. Results highest nutrient is 28.75% for c analysis, and the lowest is 15.42%, the highest N element content is 0.92% and 0.28% low, the nutrient content highest P is 0.25% and the lowest is 0.17%.Keyword: Decomposition rate, mangrove, Rhizophora apiculata, element